Online bullying : characteristics among youths in Singapore. - Soh, Grace Whee Kheng. (2010)
With the advancement of information and communications technology, online bullying has manifested itself among youths worldwide. As this endangers the well-being of online communities, therefore, it is vital to study about online bullying and its associated factors. This research aims to provide an insight on the prevalence of online bullying and personality factors that are associated with online bullying. The subjects were youths/young adults aged 16-25, and were students in Singapore. The study explored the typology of online bullying, and examined the prevalent types of online bullying and forms of electronic media where bullying is more common among youths/young adults. It also studied the relationships between gender, age, electronic media usage experiences, personality factors and online bullying to understand the characteristics of youths'/young adults' involvement in online bullying. To assess the typology of online bullying, content analysis was used to develop and refine substantive terms. The self-administrated questionnaire, which was based on established scales on personality factors, and the typology of online bullying derived in this research were deployed on a web-based application. This cross-sectional research used convenience and snowball-sampling techniques for data collection.